2021
DOI: 10.1016/j.esmoop.2021.100072
|View full text |Cite
|
Sign up to set email alerts
|

Intrapatient comparisons of efficacy in a single-arm trial of entrectinib in tumour-agnostic indications

Abstract: Background: Entrectinib is a tropomyosin receptor kinase inhibitor approved for the treatment of neurotrophic tyrosine receptor kinase (NTRK) fusion-positive solid tumours based on single-arm trials. Traditional randomised clinical trials in rare cancers are not feasible; we conducted an intrapatient analysis to evaluate the clinical benefit of entrectinib versus prior standard-of-care systemic therapies. Methods: Patients with locally advanced/metastatic NTRK fusion-positive tumours enrolled in the global pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
7
0
3
Order By: Relevance
“…In the subgroup of NSCLC, the ORR was 70% (7/10). Furthermore, intrapatient comparisons of entrectinib efficacy in the STARTRK-2 trial indicated that the ORR was higher and the median PFS was longer for entrectinib than discontinuation since the last therapy ( 83 ). Additionally, a case report showed that a patient with SQSTM1-NTRK1 fusion-positive advanced lung adenocarcinoma was treated with entrectinib, then developed partial response and had a complete remission of all brain metastases ( 41 ).…”
Section: Trk Inhibitors and Resistancementioning
confidence: 99%
“…In the subgroup of NSCLC, the ORR was 70% (7/10). Furthermore, intrapatient comparisons of entrectinib efficacy in the STARTRK-2 trial indicated that the ORR was higher and the median PFS was longer for entrectinib than discontinuation since the last therapy ( 83 ). Additionally, a case report showed that a patient with SQSTM1-NTRK1 fusion-positive advanced lung adenocarcinoma was treated with entrectinib, then developed partial response and had a complete remission of all brain metastases ( 41 ).…”
Section: Trk Inhibitors and Resistancementioning
confidence: 99%
“…The Krebs et al (2021) intra-patient comparison did not include an evaluation of any safety end points. 90…”
Section: Harmsmentioning
confidence: 99%
“…In 2018 and 2019, the tropomyosin receptor kinase inhibitors larotrectinib and entrectinib were approved for patients with solid tumors harboring neurotrophic receptor tyrosine kinase ( NTRK ) gene fusions [4, 9, 10]. Subsequently, four more drugs have been approved, of which selpercatinib is the most recent, which is a multikinase inhibitor that inhibits wild-type RET and multiple mutated RET isoforms.…”
Section: Fda-approved Tissue-agnostic Drugsmentioning
confidence: 99%